Analisis Kuat Tekan Bata Beton terhadap Penambahan Limbah Styrofoam - Isria Miharti Maherni Putri; Herol Herol; Muhammad Arief Almahdi (Prosiding Sains dan Teknologi, 2022)
Indonesia is a country with a high earthquake rate, that's because Indonesia is geographically located. So that in the development of the construction world, materials are needed that can minimize damage due to earthquakes. One indicator of a material that is able to withstand earthquake forces is its light weight but is able to withstand earthquake forces. The existence of styrofoam as waste can be used as an additional material for making materials because it has a light weight. Styrofoam is a material that is not easily decomposed by nature and the manufacture of styrofoam as a hazardous waste is the 5th largest in the world. The purpose of the study was to determine the compressive strength of concrete bricks with the addition of styrofoam. This study added styrofoam waste as a substitute for fine aggregate with a percentage of 0%, 20%, 40% and 60%. The test object was made the size of a brick, namely 23cm x 11cm x 5cm. The results of the study show that the greater the addition of styrofoam as a substitute for fine aggregate, the weight of the concrete brick is reduced and the greater the percentage of the addition of styrofoam causes the compressive strength of the concrete brick to decrease for a percentage of 60% of the concrete brick entering class 100 requirements based on SNI 15-2094-2000 with a minimum average strength of 100 kg/cm2. Keywords: Concrete Brick, Styrofoam, Compressive Strength